Kewirausahaan Pribumi dan Kegagalan Suksesi: Pelajaran dari Perusahaan Rokok Keluarga Nitisemito di Kudus - Soeharso, R. (Department of History, Faculty of Humanities, Diponegoro University, 2025)
Nitisemito was one of the indigenous entrepreneurs who successfully established a modern kretek cigarette industry in Kudus during the colonial era. Through the adoption of modern machinery technology, innovative marketing strategies, and large-scale labor management, the Cap Bal Tiga cigarette company grew into a giant in the cigarette industry of its time. Due to this company, Nitisemito's name has been enshrined as a symbol of indigenous entrepreneurship in the early 20th century. Nitisemito's success in managing his family cigarette industry demonstrates the potential emergence of an indigenous bourgeoisie amid a colonial economic structure that tended to hinder the growth of local entrepreneurs. However, the sustainability of this business experienced a decline in subsequent periods. This study aims to examine the process of the emergence of Nitisemito's business empire while explaining the factors underlying its collapse after the founder's death in 1953. This research employs historical methods, encompassing heuristic stages, source criticism, interpretation, and historiography. Historical data were obtained from archives, written sources, and interviews with Nitisemito's heirs. The results of this study indicate that the company's decline was not solely caused by changes in post-colonial economic conditions but also by internal family issues. These internal conflicts primarily related to leadership succession problems, the absence of an institutionalized management system, and tensions in relations among core family members and the extended family. This situation was further complicated by colonial political pressures on indigenous entrepreneurs and the lack of structural support for the sustainability of the Nitisemito family cigarette industry. The collapse of Nitisemito's business exemplifies the failure to form an indigenous bourgeoisie in Indonesian economic history.